2022
DOI: 10.1002/imhj.22017
|View full text |Cite
|
Sign up to set email alerts
|

Japanese infants’ attachment insecurity and externalizing/internalizing problems: Using strange situation and attachment Q‐sort methods

Abstract: According to attachment theory, an infant-mother attachment is universal, and infants who develop an insecure attachment relationship with their mother are likely to show mental health problems compared to those who develop a secure attachment relationship. These hypotheses have been empirically supported in Western cultures. However, the cross-cultural evidence is still insufficient. The purpose of this study was to examine the association between Japanese infants' attachment insecurity and mental health prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Attachment research in Asian countries such as Korea, China or Japan shows a similar proportion of secure attachment patterns as in many Western countries, but a higher proportion of insecure-ambivalent than insecure-avoidant attachment patterns in early childhood [99,101] which might be expressed in higher scores of AQS dependency. Umemura et al [102] describe that mother's striving for closeness to one's baby as expressed in "amae" or "dew" is more typical for collectivistic countries. Indeed, a study with Japanese children revealed that children's "amae" behaviors to mothers are positively associated with AQS dependency to mothers but not to attachment security [103].…”
Section: Discussionmentioning
confidence: 99%
“…Attachment research in Asian countries such as Korea, China or Japan shows a similar proportion of secure attachment patterns as in many Western countries, but a higher proportion of insecure-ambivalent than insecure-avoidant attachment patterns in early childhood [99,101] which might be expressed in higher scores of AQS dependency. Umemura et al [102] describe that mother's striving for closeness to one's baby as expressed in "amae" or "dew" is more typical for collectivistic countries. Indeed, a study with Japanese children revealed that children's "amae" behaviors to mothers are positively associated with AQS dependency to mothers but not to attachment security [103].…”
Section: Discussionmentioning
confidence: 99%
“…For the time being, it seems like this finding is an artifact of the samples available, which did not include any ambivalent children. Their representativeness of dyads from Japan is unclear, especially PRESCHOOL AND EARLY CHILDHOOD ATTACHMENT 35 given that there is evidence showing that children from Japan would be more likely to develop an ambivalent attachment due to the values and rewards of this culture (Rothbaum et al, 2000;Umemura et al, 2022).…”
Section: Significant Moderators Of the Ssp-m Distributionsmentioning
confidence: 99%